ANALISA KAWASAN KESELAMATAN OPERASI PENERBANGAN (KKOP) SESUAI RENCANA INDUK DI BANDAR UDARA JUWATA TARAKAN - Sekharisma Noorhanabila Hamzah; Cahyaning Setyarini; Wiwid Suryono (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Juwata Tarakan Airport has a 4C precision instrument aerodrome reference code which is based on the existing runway which has a length of 2,500 meters and a width of 45 meters and has 23 obstacle points. With the planning of constructing a new runway in accordance with the airport masterplan, it causes a change or shift in the Aviation Operations Safety Area of the airport. The purpose of this research is to determine the position and height of objects that emerge in the analysis of the Aviation Operations Safety Area on the review of the new runway. This study uses a descriptive method, the process of the data collection of objects was assisted by GPSmap 76CSx equipment and Hypsometer Forestry Pro. Meanwhile, the analysis process was using Google Earth, Global Mapper, and AutoCAD programs. Based on the results of the analysis that has been carried out, 2 objects were found that it was no longer an obstacle and 25 new objects appeared in the Aviation Operations Safety Area on the new runway review.